Simulation of unsteady heat and mass transport with heatline and massline in a partially heated open cavity - Rahman, M.M.; Oztop, H.F.; Mekhilef, Saad; Saidur, R.; Orfi, J. (Applied Mathematical Modelling, 2015)
A computational work is performed to investigate the transient heat and mass transfer inside a ventilated enclosure. The enclosure has two ventilation ports as inlet and outlet. Three different configurations are tested according to location of outlet ports while location of inlet port is fixed. In case 1, the outlet port is located on the top of the left vertical wall, in case 2 at the right and case 3 at the middle of the ceiling. Finite element method is employed to solve the governing equations of flow, heat and mass transfer. Also, the heatline and massline techniques are used to visualize the heat and mass transfer patterns. Obtained results show the evolution of various contours of stream function, isotherms and iso-concentrations as well as various parameters such as Nu and Sc numbers. It is found in particular that in order to reach highest heat and mass transfer rates for Gr = 10(7), the outlet port should be located near the top of the left vertical wall. On the other hand, the effect of outlet location is insignificant for the lower values of Gr. (C) 2014 Elsevier Inc. All rights reserved.